Sinergi Keberlanjutan: Mengungkap Pengaruh Green Compensation and Benefits terhadap Peningkatan Kinerja Karyawan - Ani Puspitasari; Dyah Palupiningtyas; Krisnawati SN (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This study examines the impact of Green Compensation and Benefits on employee performance and the factors influencing its effectiveness using a mixed-methods approach. Quantitative results show a significant positive relationship between employees' perceptions of these practices and their performance. Qualitative findings reveal key factors influencing effectiveness, including perceived fairness, clear communication, and alignment with personal values. This study contributes to the Green Human Resource Management (GHRM) literature by demonstrating the specific role of Green Compensation and Benefits in promoting pro-environmental behavior and enhancing employee performance. Practical implications for HR managers are emphasized, including the importance of designing fair, transparent, and value-aligned systems. Future research is suggested to investigate the generalizability of findings, employ longitudinal designs, and explore interactions between Green Compensation and Benefits and other GHRM practices. A holistic approach to GHRM can motivate employees' pro-environmental behavior and better achieve organizational sustainability goals.